Design and thermal‐hydraulic evaluation of helium‐cooled ceramic breeder blanket for China fusion engineering test reactor. (19th December 2017) - Lei, Mingzhun; Xu, Shuling; Guo, Chao; Liu, Sumei; Song, Yuntao; Lu, Kun; Pei, Kun; Xu, Kun
Summary: China Fusion Engineering Test Reactor, a fusion tokamak device, is proposed to provide complementary technology and experience for ITER and the future fusion power plant. A helium‐cooled ceramic breeder blanket concept is adopted as the candidate tritium breeding blanket for China Fusion Engineering Test Reactor. Detailed design of the blanket structure located at the outboard equatorial plane is presented. The coolant flow characters in the blanket were calculated by the theoretical method and the finite element method. The comparison of the calculated results was done, and it has a good agreement between theoretical results and simulation results. The results show that the pressure drop is 0.13 MPa and the total temperature rise is 194.6°C.